Assessing cross-sector stakeholder readiness to advance and sustain statewide behavioral integration beyond a State Innovation Model (SIM) initiative. Issue 7 (5th April 2021) - Scott, Victoria C; Gold, Stephanie B; Kenworthy, Tara; Snapper, Leslie; Gilchrist, Emma C; Kirchner, Stephanie; Wong, Shale L
Abstract: Integrated care is recognized as a promising approach to comprehensive health care and reductions in health care costs. However, the integration of behavioral health and primary care is complex and often difficult to implement. Successful and sustainable integration efforts require coordination and alignment both within health care organizations and across multiple sectors. Furthermore, implementation progress and outcomes are shaped by the readiness of stakeholders to work together toward integrated care. In the context of a Colorado State Innovation Model (SIM) effort, we examined stakeholder readiness to advance and sustain partnerships for behavioral health integration beyond the period of grant funding. Partnership readiness was assessed using the Readiness for Cross-sector Partnerships Questionnaire (RCP) in spring 2019. Participants from 67 organizations represented seven sectors: government, health care, academic, practice transformation, advocacy, payer, and other. RCP analyses indicated a moderate level of readiness among Colorado stakeholders for partnering to continue the work of behavioral health integration initiated by SIM. Stakeholders indicated their highest readiness levels for general capacity and lowest for innovation-specific capacity. Five thematic categories emerged from the open-ended questions pertaining to partnership experiences: (a) collaboration and relationships, (b) capacity and leadership, (c) measurement and outcomes, (d) financing integrated care, and (e) sustainability of the cross-sector partnership. Partnering across sectors to advance integrated behavioral health and create more equitable access to services is inherently complex and nonlinear in nature. The RCP usefully identifies opportunities to strengthen the sustainability of integrated care efforts. Abstract : Participants representing seven sectors in Colorado indicated a moderate level of readiness to advance and sustain partnerships for state-wide behavioral integration. The Readiness for Cross-sector Partnerships questionnaire usefully identifies opportunities to strengthen sustainability of integrated care efforts.